Grower and operational characteristics of US passion fruit farmers - Benedict C. Posadas; Eric T. Stafne; Trent Blare; Laura Downey; Joshua Anderson; Jonathan Crane; Romina Gazis; Ben Faber; Dara G. Stockton; Daniel Carrillo; J. Pablo Morales-Payan; Manjul Dutt; et al. (Technology in Horticulture)
In the United States and its territories, passion fruit production has increased steadily since the 2002 USDA agriculture census; however, little is known about the reported production areas and how the industry functions. This report details the results of a survey conducted in 2022 of passion fruit producers in the United States, including Puerto Rico and Hawaii. The aim was to collect data on farm operational characteristics, sales data, and grower demographics. Forty-four surveys were completed, with Florida having the most responses (21), followed by Puerto Rico (12) and California (six). Hawaii, Louisiana, Mississippi, and the Virgin Islands completed the remainder. This sample was 12% of the 364 passion fruit farms reported in 2017. The acreage dedicated to passion fruit production averaged 1.7 acres in 2019 and 2.1 acres in 2020 per farm, with most occurring in Florida. A box of fruit had around 30 fruits and a mean price of \begin{document}${\$} $\end{document}3.08 per lb. About 83% of the harvested passion fruit was sold fresh, although more than 50% of farms included sales of value-added products. Of the fresh fruit sold, 34.9% were sold directly to consumers. The respondents averaged 53.2 years old. More than eight out of ten respondents completed at least a college degree. Half the growers considered themselves Hispanic, while almost two-thirds were white, followed by multiple racial origins and American Indian. This data developed a greater understanding of the passion fruit industry within the US and will frame future projects to help grow this valuable specialty crop.